Strategic Planning for Education Quality Improvement Based on SWOT Analysis: A Case Study - Atin Chusniyah; Rino Ariyanto Akhmad; Heldy Ramadhan Putra P (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2023)
This research examines internal and external environmental factors and builds strategic planning to improve educational quality. This study employs a qualitative descriptive approach to gain an in-depth image of the research object at SMP Muhammadiyah 14 Sambi Boyolali. Data gathering methods included interviews, observation, and document analysis—data analysis methods included data reduction, data presentation, and verification. According to the research findings, the internal analysis of SMP Muhammadiyah 14 Sambi Boyolali has more advantages than negatives. Opportunities outnumber risks in external assessments. The numerous benefits and prospects demonstrate that the school can establish obvious and demonstrable school quality. Strategic planning based on the SO-WO-ST-WT analysis can include developing the school environment into an ideal learning community, conducting human resource training and development, forming achievement clubs, improving the quality of school services, forming an organizational school activity evaluation team, utilizing funds effectively and efficiently, establishing resource sharing, and developing school branding. The theoretical contribution of this research can help the scientific understanding of Islamic education management. It can be a helpful tool for understanding the role of schools in enhancing educational quality.